Dakwah Strategies through the Study of Ta’lim al-Muta’allim in the Moral Development of Santri - Nur Ali Said Zakariya Al Ansori; Rosyidi Rosyidi; Chairul Absari (Al Yazidiy Jurnal Sosial Humaniora dan Pendidikan, 2024)
Islamic boarding schools (pondok pesantren), as traditional Islamic educational institutions, play a crucial role in shaping the moral character of students (santri). The classical Islamic text Ta’lim al-Muta’allim by Shaykh al-Zarnuji has long served as a fundamental reference for instilling ethical values and proper manners in the pursuit of knowledge. This study aims to examine the da'wah strategies implemented at Pondok Pesantren Al-Muqri Assalafi through the teaching of Ta’lim al-Muta’allim, in an effort to foster students' character development. Employing a qualitative descriptive approach, data were collected through observation, interviews, and documentation involving male students and the pesantren's management. The findings indicate that the da'wah strategies consist of four primary stages: planning the delivery of da'wah, providing moral guidance, monitoring student behavior, and conducting regular evaluations through consultative assemblies. Supporting factors identified include the enthusiasm of both teachers and students, the availability of substitute teachers, and environmental support; while inhibiting factors include student absenteeism, external environmental influences, and excessive familiarity between students and teachers. Overall, these strategies have proven effective in shaping morally upright students capable of serving as role models in society.